2022
DOI: 10.1038/s41419-022-04597-z
|View full text |Cite
|
Sign up to set email alerts
|

Early differential responses elicited by BRAFV600E in adult mouse models

Abstract: The BRAF gene is frequently mutated in cancer. The most common genetic mutation is a single nucleotide transition which gives rise to a constitutively active BRAF kinase (BRAFV600E) which in turn sustains continuous cell proliferation. The study of BRAFV600E murine models has been mainly focused on the role of BRAFV600E in tumor development but little is known on the early molecular impact of BRAFV600E expression in vivo. Here, we study the immediate effects of acute ubiquitous BRAFV600E activation in vivo. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 65 publications
1
14
0
Order By: Relevance
“…There are other cellular mechanisms not directly involved in mitogenic signaling pathways that might influence the outcome of Braf mutation. In a recent study comparing immediate effects of ubiquitous BRAF V600E expression in mice, 47 a DNA damage response was evident in several organs including the lungs but not in the thyroid. Although these organ differences were not further investigated, it is possible that cells’ ability to cope with DNA damage on oncogene activation might differentially influence tumorigenesis in lung and thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…There are other cellular mechanisms not directly involved in mitogenic signaling pathways that might influence the outcome of Braf mutation. In a recent study comparing immediate effects of ubiquitous BRAF V600E expression in mice, 47 a DNA damage response was evident in several organs including the lungs but not in the thyroid. Although these organ differences were not further investigated, it is possible that cells’ ability to cope with DNA damage on oncogene activation might differentially influence tumorigenesis in lung and thyroid.…”
Section: Discussionmentioning
confidence: 99%
“…Based on our observations, we conclude that the differences in telomere length in DN are the result of the differential activation of OIS and RS depending on the initiating driver mutation and represent two orthogonal senescence mechanisms limiting the progression of dysplastic nevi. However, an alternative explanation could be that the cell state of the melanocyte in which the driver mutation arises may also affect the fate of the nascent neoplasm and which tumor suppressor mechanisms become engaged, explaining the observed differences in telomere length and p16 accumulation (34,35).…”
Section: Discussionmentioning
confidence: 99%
“…Based on computational high-throughput virtual screening followed by in vitro analysis, in this work, we predicted compound CB-006-3 as a dual inhibitor of PI3K/BRAF V600E kinases. Previous studies have shown that a majority of melanoma cancers show BRAF V600E activated mutation, therefore targeting BRAF V600E can control cell proliferation to a significant extent [17]. Since the PI3K pathway is also implicated in a majority of the melanomas, studies have shown that targeting both PI3K and BRAF V600E show improved protection as against the traditional chemotherapy agents [18].…”
Section: Discussionmentioning
confidence: 99%